CT Scan Mapping of Splenic Flexure in Relation to Spleen and its Clinical Implications. Issue 5 (May 2016) - Saber, Alan A.; Dervishaj, Ornela; Aida, Samer S.; Christos, Paul J.; Dakhel, Mahmoud
Splenic flexure mobilization is a challenging step during left colon resection. The maneuver places the spleen at risk for injury. To minimize this risk, we conducted this study for CT scan mapping of splenic flexure in relation to the spleen. One hundred and sixty CTscans of abdomen were reviewed. The level of the splenic flexure was determined in relation to hilum and lower pole of spleen. These levels were compared with patient demographics. Statistical analysis was performed using Fisher's exact test. The splenic flexure was above the hilum of the spleen in 95 patients (67.86%), at the splenic hilum level in 11 patents (7.88%), between the hilum and lower pole of the spleen in 12 (8.57%), at the lower pole of the spleen in 15 (10.7%) patients and 7 (5%) patients has a splenic flexure that lied below the lower pole of the spleen. Patient demographics showed no statistical significance in regard to splenic flexure location. Splenic flexure lies above the hilum of the spleen in majority of patients. This should be considered as part of operative strategies for left colon resection.